Amdal Regulations In Indonesia Concerning Environmental Management and Preservation Law No. 32 of 2009 - Zaini, Ahmad (Journal of Law, Politic and Humanities, 2024)
Decree issued by the environment minister Number 17 of 2001 regarding the kinds of company operations and initiatives that must carried out accompanied by an environmental impact analysis. The purpose of this study is to establish of EIA as a guideline that should be made before the process from pre-construction to production. This research has made people realize how important environmental issues and natural resources are for the survival of all creatures on Earth, including humans. Like the environment, it has limitations to provide life to humans. Environmental conservation is characterized as the maintenance of the environment as it is, but paradoxically, development utilizes it. On the contrary, those developments have made human life much better. Today, it seems that humans are facing difficulties. The age must accelerate development so as not to be left behind, but it must also maintain the stability of the environment so as not to destroy it.